An electrocatalyst, a method for preparing the same, and use thereof in electrocatalytic glycol to glycolate
Patent Information
- Application Number
- CN202311313061.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-10-11
AI Technical Summary
但目前公开的可用于该反应体系的高性能催化剂仍然较少,难以满足应用的需求
[0069]本发明提供了一种电催化剂及其制备方法和在电催化乙二醇制备乙醇酸盐中的应用。通过该电催化剂的电催化氧化作用,可以在常温常压下从废弃塑料PET或者乙二醇出发制备得到高附加值化学品乙醇酸钠,不仅从根本上解决了生产乙醇酸的剧毒原料问题,还实现了废弃塑料PET的资源化与能源化利用,因此相比于现有工业技术具有更大的经济效益,适合产业化和大规模推广。
Smart Images

Figure CN117448880B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical catalysis technology, specifically including an electrocatalyst, its preparation method, and its application in the electrocatalytic preparation of glycolate from ethylene glycol. Background Technology
[0002] Glycolic acid, a commonly used chemical raw material, is widely applied in many industrial fields, such as chemical cleaning, disinfectants, daily chemical products, biodegradable materials, and electroplating surface treatment agents. However, the synthesis cost of glycolic acid is relatively high. This is mainly because current industrial glycolic acid production uses chloroacetic acid as a raw material, which is then esterified with methanol to produce methyl glycolate, followed by purification through distillation and hydrolysis. However, chloroacetic acid is a highly toxic and corrosive substance, classified as a Class 6 hazardous chemical. Therefore, low-cost, large-scale production of glycolic acid presents significant challenges.
[0003] Electrocatalytic synthesis of glycolic acid involves the selective oxidation of ethylene glycol to glycolic acid using a suitable electrocatalyst under electrical drive. This method effectively addresses the issue of highly toxic raw materials in glycolic acid production and provides a new direction for its industrial-scale production. Furthermore, ethylene glycol can be released from waste PET plastic through alkaline hydrolysis; therefore, glycolic acid can also be prepared using waste PET as a raw material, which is highly beneficial for the recycling and economic value enhancement of waste PET. However, currently, there are still relatively few publicly available high-performance catalysts suitable for this reaction system, making it difficult to meet application requirements. Summary of the Invention
[0004] To address the aforementioned problems in the prior art, the first objective of this invention is to provide an electrocatalyst. This electrocatalyst exhibits high selectivity and catalytic activity in the electrocatalytic preparation of glycolate from ethylene glycol, with a glycolate selectivity ≥90% and an electrocatalytic activity reaching 220-380 mA / cm². 2 Compared to existing industrial technologies, it has greater economic benefits and is suitable for industrialization and large-scale promotion.
[0005] A second objective of this invention is to provide a method for preparing the electrocatalyst as described above.
[0006] A third object of the present invention is to provide an electrolytic cell system comprising the electrocatalyst described above.
[0007] A fourth objective of this invention is to provide a method for the electrocatalytic preparation of glycolate from ethylene glycol.
[0008] To achieve the first objective mentioned above, the technical solution adopted by the present invention includes:
[0009] This invention discloses an electrocatalyst comprising a foamed metal and an active ingredient, wherein the active ingredient is Pd / Co. x Cr y O z The active ingredient contains Co x Cr y O z Metallic Pd was loaded onto the surface of foamed metal in the form of nanosheets, and metallic Pd was loaded onto Co in the form of nanoparticles. x Cr y O z surface;
[0010] Where x takes values from 0 to 3, y takes values from 0 to 2, and z takes values from 0 to 4, and x, y, and z are not 0.
[0011] Furthermore, the active ingredient contains Co x Cr y O z The loading on the foamed metal is 40-200 mg / cm³. 2 For example, Co x Cr y O z The loading amount on the foamed metal can be 40 mg / cm³. 2 50mg / cm 2 60mg / cm 2 70mg / cm 2 80mg / cm 2 90mg / cm 2 100mg / cm 2 110mg / cm 2 120mg / cm 2 130mg / cm 2 140mg / cm 2 150mg / cm 2 160mg / cm 2 170mg / cm 2 180mg / cm 2 190mg / cm 2 200mg / cm 2 etc.
[0012] Furthermore, the active ingredient, metal Pd, is present in the Co... x Cr y O z The loading capacity is 1-5 mg / cm³ 2 For example, the metal Pd in the Co x Cr y O zThe loading capacity can be 1 mg / cm³ 2 2mg / cm 2 3mg / cm 2 4mg / cm 2 5mg / cm 2 etc.
[0013] Furthermore, the particle size of the noble metal Pd is in the nanometer range, for example, 10-50 nm.
[0014] Furthermore, the foamed metal includes, but is not limited to, at least one of foamed nickel, foamed copper, foamed iron, and foamed cobalt; preferably, foamed nickel.
[0015] To achieve the second objective mentioned above, the technical solution adopted by the present invention includes:
[0016] This invention discloses a method for preparing the electrocatalyst as described above, comprising the following steps:
[0017] Co is prepared by dissolving cobalt salts, chromium salts, and an alkali in an organic solvent, then immersing a foamed metal in the solution, and using a solvothermal method. x Cr y (OH) 2z Loaded foamed metal;
[0018] Co x Cr y (OH) 2z The loaded metal foam was placed in a palladium salt solution for a displacement reaction to obtain Pd / Co. x Cr y (OH) 2z Loaded foamed metal;
[0019] Pd / Co x Cr y (OH) 2z The supported metal foam was calcined to prepare the electrocatalyst, namely Pd / Co. x Cr y O z / Foam metal.
[0020] Furthermore, the cobalt salt includes, but is not limited to, one or more of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, and cobalt acetylacetonate; the chromium salt includes, but is not limited to, one or more of chromium nitrate, chromium acetate, chromium chloride, chromium sulfate, and chromium acetylacetonate; and the alkali is selected from, or one or more of urea, ammonia, sodium hydroxide, and potassium hydroxide.
[0021] Furthermore, during feeding, the molar ratio of the cobalt salt, chromium salt, and alkali is 0.1-3:0.1-2:4-20; for example, the molar ratio of the cobalt salt, chromium salt, and alkali can be 1:1:10, 1:2:10, 1:4:10, etc.
[0022] Furthermore, the organic solvent includes, but is not limited to, ethanol, methanol, acetone, acetonitrile, etc.; the concentration of the cobalt salt in the organic solvent is 3-30 mM, and the concentration of the chromium salt in the organic solvent is 3-30 mM.
[0023] Furthermore, the reaction temperature of the solvothermal method is 150-220℃, and the reaction time is 5-20h.
[0024] Furthermore, the concentration of the palladium salt solution is 20-40 mM; for example, the concentration of the palladium salt solution can be 20 mM, 25 mM, 30 mM, 35 mM, 40 mM, etc.
[0025] Furthermore, the palladium salts contained in the palladium salt solution include, but are not limited to, PdCl2, Pd(NO3)2, Pd(SO4)2, H2PdCl4, etc.; due to the redox potential difference between palladium ions and the metal ions on the foam metal, a displacement reaction can occur, and after a certain reaction time, the Pd in the solution... 2+ Ions can be reduced and loaded onto Co. x Cr y O z The electrocatalyst is thus prepared by applying it to the surface.
[0026] Furthermore, the foamed metal needs to be pre-treated to ensure its surface is clean and free of impurities. The operation steps can be as follows:
[0027] The foamed metal was ultrasonically cleaned sequentially with acetone, ethanol, and distilled water, then ultrasonically treated in 1-3.0 mol / L hydrochloric acid for more than 30 minutes, followed by ultrasonic cleaning in deionized water and ethanol several times, and finally dried for later use.
[0028] Those skilled in the art will understand that when foam metal is placed in a high-pressure reactor for solvothermal reaction, it should be inserted obliquely into the polytetrafluoroethylene liner as much as possible to ensure that precursors can grow on both sides of the foam metal.
[0029] Furthermore, the calcination temperature is 450-500℃, and the calcination time is 2-6h.
[0030] To achieve the third objective mentioned above, the technical solution adopted by the present invention includes:
[0031] This invention discloses an electrolytic cell system for the electrocatalytic preparation of glycolate from ethylene glycol, the electrolytic cell system comprising the electrocatalyst described above and an alkaline electrolyte containing ethylene glycol.
[0032] Furthermore, the alkaline electrolyte is obtained by alkaline hydrolysis of waste PET plastic or by directly adding ethylene glycol to an alkaline solution for preparation.
[0033] When the alkaline electrolyte is obtained by alkaline hydrolysis of waste PET plastic, the specific preparation steps of the alkaline electrolyte can be as follows:
[0034] Waste PET plastic is dissolved in an alkaline solution and heated and refluxed at 50-100℃ (i.e., alkaline hydrolysis reaction) for 5-20 hours. After reflux, solid-liquid separation is performed to obtain an alkaline electrolyte containing ethylene glycol.
[0035] Furthermore, the waste plastic PET includes, but is not limited to, one or more of bottle-grade PET, film-grade PET, and fiber-grade PET.
[0036] Furthermore, in the alkaline electrolyte containing ethylene glycol, the molar ratio of ethylene glycol to alkali is 1:1-5.
[0037] Furthermore, the alkali is potassium hydroxide and / or sodium hydroxide. When the alkali is sodium hydroxide, it is more conducive to the separation and purification of the product.
[0038] To achieve the fourth objective mentioned above, the technical solution adopted by the present invention includes:
[0039] This invention discloses a method for electrocatalytically preparing glycolate from ethylene glycol, comprising the following steps:
[0040] An anode catalyst, a cathode catalyst, and an alkaline electrolyte containing ethylene glycol are assembled into a two-electrode electrolytic cell. An electrocatalytic reaction is carried out by applying a voltage. The ethylene glycol is oxidized at the anode to form glycolate, while high-purity hydrogen gas with an equal coulombic charge can be generated at the cathode.
[0041] The anode catalyst is the Pd / Co electrocatalyst described above. x Cr y O z / Foam metal.
[0042] Furthermore, the cathode catalyst includes, but is not limited to, foam metal and / or supported catalyst; the supported catalyst is selected from at least one of platinum-supported foam metal, platinum alloy-supported foam metal, nickel phosphide-supported foam metal, and cobalt phosphide-supported foam metal.
[0043] Furthermore, the alkaline electrolyte is obtained by hydrolyzing waste PET plastic or by directly adding ethylene glycol to an alkaline solution for preparation.
[0044] When the alkaline electrolyte is obtained by hydrolyzing waste PET plastic, the specific preparation steps of the alkaline electrolyte can be as follows:
[0045] Waste PET plastic is dissolved in an alkaline solution and heated and refluxed (i.e., hydrolysis) at 50-100℃ for 5-20 hours. After reflux, solid-liquid separation is performed to obtain an alkaline electrolyte containing ethylene glycol.
[0046] Furthermore, the waste plastic PET includes, but is not limited to, one or more of bottle-grade PET, film-grade PET, and fiber-grade PET.
[0047] Furthermore, in the alkaline electrolyte containing ethylene glycol, the molar ratio of ethylene glycol to alkali is 1:1-5.
[0048] Furthermore, the alkali is potassium hydroxide and / or sodium hydroxide. When the alkali is sodium hydroxide, it is more conducive to the separation and purification of the product.
[0049] Furthermore, during the electrocatalytic reaction, the cell voltage is 1-1.6V.
[0050] Furthermore, after the electrocatalytic reaction, technicians can separate and purify the oxidation products according to experimental needs, specifically including the following steps:
[0051] The solution after electrolysis (the electrolyte containing glycolate) is decolorized with activated carbon, dried, washed, dissolved, filtered, and recrystallized to obtain separated and purified glycolate. The separation and purification operation of the present invention can not only effectively separate glycolate from the electrolyte after the reaction, but also obtain high-purity glycolate, which can be directly used in the industrial production of glycolic acid without other purification treatments.
[0052] Furthermore, the washing solution used is at least one of dichloromethane, methanol, ethanol, and water.
[0053] To achieve the fourth objective mentioned above, the technical solution adopted by the present invention includes:
[0054] This invention discloses a method for electrocatalytically preparing glycolate from ethylene glycol, comprising the following steps:
[0055] A three-electrode electrolytic cell is assembled with a working electrode, a counter electrode, a reference electrode, and an alkaline electrolyte containing ethylene glycol. An electrocatalytic reaction is carried out by applying voltage. The ethylene glycol is oxidized to glycolate at the working electrode, while high-purity hydrogen gas with an equal coulombic quantity is generated at the counter electrode.
[0056] The working electrode comprises the electrocatalyst according to any one of claims 1-4.
[0057] Furthermore, the counter electrode is a Pt sheet, and the reference electrode is Hg / HgO.
[0058] Furthermore, the alkaline electrolyte is obtained by hydrolyzing waste PET plastic or by directly adding ethylene glycol to an alkaline solution for preparation.
[0059] When the alkaline electrolyte is obtained by hydrolyzing waste PET plastic, the specific preparation steps of the alkaline electrolyte can be as follows:
[0060] Waste PET plastic is dissolved in an alkaline solution and heated and refluxed at 50-100℃ (i.e., alkaline hydrolysis reaction) for 5-20 hours. After reflux, solid-liquid separation is performed to obtain an alkaline electrolyte containing ethylene glycol.
[0061] Furthermore, the waste plastic PET includes, but is not limited to, one or more of bottle-grade PET, film-grade PET, and fiber-grade PET.
[0062] Furthermore, in the alkaline electrolyte containing ethylene glycol, the molar ratio of ethylene glycol to alkali is 1:1-5.
[0063] Furthermore, the alkali is potassium hydroxide and / or sodium hydroxide. When the alkali is sodium hydroxide, it is more conducive to the separation and purification of the product.
[0064] Furthermore, during the electrocatalytic reaction, the applied voltage is in the range of 0.6-1V vs. RHE.
[0065] Furthermore, after the electrocatalytic reaction, technicians can separate and purify the oxidation products according to experimental needs, specifically including the following steps:
[0066] The solution after electrolysis (the electrolyte containing glycolate) is decolorized with activated carbon, dried, washed, dissolved, filtered, and recrystallized to obtain separated and purified glycolate. The separation and purification operation of the present invention can not only effectively separate glycolate from the electrolyte after the reaction, but also obtain high-purity glycolate, which can be directly used in the industrial production of glycolic acid without other purification treatments.
[0067] Furthermore, the washing solution used is at least one of dichloromethane, methanol, ethanol, and water.
[0068] Beneficial effects of this invention:
[0069] This invention provides an electrocatalyst, its preparation method, and its application in the electrocatalytic preparation of glycolate from ethylene glycol. Through the electrocatalytic oxidation of this electrocatalyst, sodium glycolate, a high-value-added chemical, can be prepared from waste PET plastic or ethylene glycol at room temperature and pressure. This not only fundamentally solves the problem of highly toxic raw materials in the production of glycolic acid but also realizes the resource and energy utilization of waste PET plastic. Therefore, compared with existing industrial technologies, it has greater economic benefits and is suitable for industrialization and large-scale promotion.
[0070] In a three-electrode system, sodium glycolate can be collected at the working electrode via an electrocatalytic reaction. With optimized conditions, the selectivity for sodium glycolate can reach over 90%, and the electrocatalytic activity can reach 220-380 mA / cm². 2 . Attached Figure Description
[0071] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.
[0072] Figure 1 The Pd / Co prepared in Example 1 is shown. x Cr y O z Scanning electron microscope image of Nifoam electrocatalyst.
[0073] Figure 2 Cyclic voltammetry curves of the electrocatalysts prepared in Examples 2, 4, 5, and Comparative Example 1 for the electrocatalytic oxidation of an alkaline electrolyte containing ethylene glycol are shown.
[0074] Figure 3 The chronoamperometric curves for electrocatalytic oxidation in Example 2 are shown, with an electrode potential of 0.7 V vs. RHE.
[0075] Figure 4 The electrocatalytic oxidation product of ethylene glycol in Example 2 is shown. 1 H NMR spectrum.
[0076] Figure 5 The electrocatalytic oxidation product of ethylene glycol in Example 2 is shown. 13 C NMR spectrum.
[0077] Figure 6 This shows ethylene glycol after alkaline hydrolysis of waste PET plastic. 1 H NMR spectrum.
[0078] Figure 7 Cyclic voltammetry curves of the electrocatalyst prepared in Example 3 for the electrocatalytic oxidation of an alkaline electrolyte containing ethylene glycol are shown.
[0079] Figure 8The chronoamperometric curves for electrocatalytic oxidation in Example 3 are shown, with an electrode potential of 0.7 V vs. RHE.
[0080] Figure 9 The electrocatalytic oxidation product of ethylene glycol in Example 3 is shown. 1 H NMR spectrum.
[0081] Figure 10 The electrocatalytic oxidation product of ethylene glycol in Example 3 is shown. 13 C NMR spectrum. Detailed Implementation
[0082] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments and accompanying drawings, further clarifies the invention. It should be understood that the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0083] In addition, unless otherwise specified, all raw materials used in this invention can be obtained commercially available. Any range described in this invention includes the end value and any value between the end values, as well as any subrange formed by the end value or any value between the end values.
[0084] In this specific embodiment, there is no particular limitation on the time of the electrocatalytic reaction; those skilled in the art can determine this based on nuclear magnetic resonance imaging. 1 Qualitative or quantitative analysis of the electrolytic product glycolate is performed using chromatographic, gas chromatographic, or XRD spectra to determine the reaction progress and completion time.
[0085] In the following examples, the recovery rate is calculated as follows: Recovery rate (%) = Actual yield of product / Theoretical yield of product × 100%.
[0086] Example 1: Pd / Co x Cr y O z Preparation of Nifoam
[0087] 120 mg of cobalt acetylacetone, 230 mg of chromium acetylacetone, and 70 mg of urea were added to 40 mL of ethanol and stirred until dissolved. Then, a 1 cm × 2 cm metallic nickel foam was immersed in the solution and transferred to a high-pressure reactor for a solvothermal reaction at 200 °C for 12 h. After the reaction, Co was obtained. x Cr y (OH) 2z / Nifoam.
[0088] Co x Cr y(OH) 2z Nifoam was impregnated into a 30 mM, 2 mL H₂PdCl₄ solution for a displacement reaction. The [PdCl₄] in the solution... 2- The ions are reduced to Pd 0 And loaded to Co x Cr y (OH) 2z Pd / Co was obtained from the surface of nickel foam. x Cr y (OH) 2z / Nifoam.
[0089] Pd / Co x Cr y (OH) 2z Nifoam was calcined at 450℃ for 4 hours to finally prepare Pd / Co. x Cr y O z / Nifoam electrocatalyst, tested Co x Cr y O z The loading on nickel foam is 75 mg / cm³. 2 Metallic Pd in Co x Cr y O z The loading capacity is 3 mg / cm³. 2 .
[0090] Figure 1 Pd / Co x Cr y O z Scanning electron microscope (SEM) image of the Nifoam electrocatalyst, from which Co can be seen. x Cr y O z Metallic Pd was vertically loaded onto the surface of nickel foam in the form of nanosheet arrays, and metallic Pd was loaded onto Co in the form of nanoparticles. x Cr y O z Nanosheet tip.
[0091] Example 2: Pd / Co x Cr y O z Nifoam electrocatalyst for the electrocatalytic conversion of ethylene glycol to glycolate
[0092] 1) Preparation of alkaline ethylene glycol solution
[0093] Prepare an ethylene glycol sodium hydroxide solution by dissolving 8g of NaOH powder and 5.5ml of ethylene glycol in 50ml of water.
[0094] 2) Electrocatalytic production of glycolates from ethylene glycol
[0095] Pd / Co prepared in Example 1 x Cr y O z Nifoam was used as an electrocatalyst for the electrocatalytic oxidation of ethylene glycol. The electrocatalytic oxidation of ethylene glycol was controlled using a CHI660E electrochemical workstation, employing an H-type electrolytic cell with a three-electrode configuration. The working electrode was the Pd / Co alloy prepared in Example 1. x Cr y O z The catalyst is a Nifoam, the counter electrode is a Pt sheet electrode, the reference electrode is a Hg / HgO electrode, and the electrolyte is an alkaline electrolyte containing ethylene glycol. In the alkaline electrolyte, the concentration of ethylene glycol is controlled at 2M and the concentration of NaOH is 4M.
[0096] All potentials in the electrocatalytic oxidation of ethylene glycol were calibrated with reference to a reversible hydrogen electrode (RHE). Pd / Co x Cr y O z The geometric surface area of the Nifoam electrocatalyst is 1 cm². 2 and using 1cm 2 The current density was calculated using the geometric surface area. All experiments were conducted at room temperature and pressure, and their cyclic voltammetry curves are shown below. Figure 2 As shown, when the applied voltage is controlled at 0.7V vs. RHE, its electrolysis curve is as follows. Figure 3 As shown.
[0097] 3) Qualitative and quantitative analysis of sodium glycolate
[0098] At a current density of 380 mA / cm 2 After several hours of electrocatalytic oxidation, a portion of the electrolyte was collected and then analyzed by aqueous NMR. 1 H and 13 The product sodium glycolate was qualitatively and quantitatively analyzed by method C. (See attached table for results.) Figure 4 and Figure 5 Calculations show that the selectivity of sodium glycolate is 90%.
[0099] Example 3: Pd / Co x Cr y O z Nifoam electrocatalyst for the electrocatalytic conversion of ethylene glycol to glycolate
[0100] 1) Hydrolysis of waste PET plastic:
[0101] 10g of waste PET plastic was added to a 100mL NaOH solution (5M concentration), and the mixture was refluxed at 50-100℃ for 5-20 hours. After the reflux reaction was complete, the sodium terephthalate solid product was separated and filtered, and an alkaline electrolyte containing ethylene glycol was obtained. Figure 6 ).
[0102] 2) Electrocatalytic production of glycolates from ethylene glycol
[0103] Pd / Co prepared in Example 1 x Cr y O z Nifoam was used as an electrocatalyst for the electrocatalytic oxidation of ethylene glycol. The electrocatalytic oxidation of ethylene glycol was controlled using a CHI660E electrochemical workstation, employing an H-type electrolytic cell with a three-electrode configuration. The working electrode was the Pd / Co alloy prepared in Example 1. x Cr y O z The catalyst is a Nifoam, the counter electrode is a Pt sheet electrode, the reference electrode is a Hg / HgO electrode, and the electrolyte is an alkaline electrolyte containing ethylene glycol. In the alkaline electrolyte, the concentration of ethylene glycol is controlled at 0.5M and the concentration of NaOH is 4M.
[0104] All potentials in the electrocatalytic oxidation of ethylene glycol were calibrated with reference to a reversible hydrogen electrode (RHE). Pd / Co x Cr y O z The geometric surface area of the Nifoam electrocatalyst is 1 cm². 2 and using 1cm 2 The current density was calculated using the geometric surface area. All experiments were conducted at room temperature and pressure, and their cyclic voltammetry curves are shown below. Figure 7 As shown, when the applied voltage is controlled at 0.7V vs. RHE, its electrolysis curve is as follows. Figure 8 As shown.
[0105] 3) Qualitative and quantitative analysis of sodium glycolate
[0106] At a current density of 220 mA / cm 2 After several hours of electrocatalytic oxidation, a portion of the electrolyte was taken and then passed through an aqueous phase. 1 H and 13 Qualitative and quantitative analysis of the product sodium glycolate was performed by C10 NMR spectroscopy. (See attached table for results.) Figure 9 and Figure 10 Calculations show that the selectivity of sodium glycolate is 91%.
[0107] Example 4: Pd / Co x Cr y Oz Nifoam electrocatalyst for the electrocatalytic conversion of ethylene glycol to glycolate
[0108] 60 mg of cobalt acetylacetone, 230 mg of chromium acetylacetone, and 70 mg of urea were added to 40 mL of ethanol and stirred until dissolved. Then, a 1 cm × 2 cm metallic nickel foam was immersed in the solution and transferred to a high-pressure reactor for a solvothermal reaction at 200 °C for 12 h. After the reaction, Co was obtained. x Cr y (OH) 2z / Nifoam.
[0109] Co x Cr y (OH) 2z Nifoam was impregnated into a 30 mM, 2 mL H₂PdCl₄ solution for a displacement reaction. The [PdCl₄] in the solution... 2- The ions are reduced to Pd 0 And loaded to Co x Cr y (OH) 2z Pd / Co was obtained from the surface of nickel foam. x Cr y (OH) 2z / Nifoam.
[0110] Pd / Co x Cr y (OH) 2z Nifoam was calcined at 450℃ for 4 hours to finally prepare Pd / Co. x Cr y O z / Nifoam electrocatalyst.
[0111] The prepared catalyst Pd / Co x Cr y O z / Nifoam was used in the electrocatalytic oxidation of ethylene glycol, and the electrocatalytic process was carried out according to the steps of Example 2. Its optimal catalytic activity was 44% of that in Example 1. Figure 2 ).
[0112] Example 5: Pd / Co x Cr y O z Nifoam electrocatalyst for the electrocatalytic conversion of ethylene glycol to glycolate
[0113] 120 mg of cobalt acetylacetone, 120 mg of chromium acetylacetone, and 70 mg of urea were added to 40 mL of ethanol and stirred until dissolved. Then, a 1 cm × 2 cm metallic nickel foam was immersed in the solution and transferred to a high-pressure reactor for a solvothermal reaction at 200 °C for 12 h. After the reaction, Co was obtained. x Cr y (OH) 2z / Nifoam.
[0114] Co x Cr y (OH) 2z Nifoam was impregnated into a 30 mM, 2 mL H₂PdCl₄ solution for a displacement reaction. The [PdCl₄] in the solution... 2- The ions are reduced to Pd 0 And loaded to Co x Cr y (OH) 2z Pd / Co was obtained from the surface of nickel foam. x Cr y (OH) 2z / Nifoam.
[0115] Pd / Co x Cr y (OH) 2z Nifoam was calcined at 450℃ for 4 hours to finally prepare Pd / Co. x Cr y O z / Nifoam electrocatalyst.
[0116] Comparative Example 1
[0117] 20 mg of commercially available Pd / C catalyst was dispersed in 2 ml of a mixed solution (the mixed solution consisted of water, ethanol, and Nafion solution in a volume ratio of 1:0.1:0.02) to obtain a slurry. The slurry was then drop-coated onto the Co catalyst prepared in Example 1. x Cr y O z Nifoam surface, dried, thus preparing Pd / C / Co x Cr y O z / Nifoam catalyst, the prepared Pd / C / Co catalyst x Cr y O z / Nifoam was used in the electrocatalytic oxidation of ethylene glycol, and the electrocatalytic process was carried out according to the steps of Example 3. Its optimal catalytic activity was 19% of that in Example 1. Figure 2 ).
[0118] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing an electrocatalyst, characterized in that, Includes the following steps: Co is prepared by dissolving cobalt salts, chromium salts, and an alkali in an organic solvent, then immersing a foamed metal in the solution, and using a solvothermal method. x Cr y (OH) 2z Loaded foamed metal; Co x Cr y (OH) 2z The loaded metal foam was placed in a palladium salt solution for a displacement reaction to obtain Pd / Co. x Cr y (OH) 2z Loaded foamed metal; Pd / Co x Cr y (OH) 2z The electrocatalyst is prepared by calcining a supported metal foam; the electrocatalyst comprises a metal foam and an active component, wherein the active component is Pd / Co. x Cr y O z The active ingredient contains Co x Cr y O z Metallic Pd was loaded onto the surface of foamed metal in the form of nanosheets, and metallic Pd was loaded onto Co in the form of nanoparticles. x Cr y O z surface; Where x takes values from 0 to 3, y takes values from 0 to 2, and z takes values from 0 to 4, and x, y, and z are not 0; The foam metal is selected from nickel foam.
2. The preparation method according to claim 1, characterized in that, The cobalt salt is selected from one or more of cobalt nitrate, cobalt acetate, cobalt chloride, cobalt sulfate, and cobalt acetylacetonate; the chromium salt is selected from one or more of chromium nitrate, chromium acetate, chromium chloride, chromium sulfate, and chromium acetylacetonate; and the alkali is selected from one or more of urea, ammonia, sodium hydroxide, and potassium hydroxide.
3. The preparation method according to claim 1, characterized in that, The concentration of the palladium salt solution is 20-40 mM.
4. An electrocatalyst, characterized in that, It is prepared by the preparation method according to any one of claims 1-3.
5. The electrocatalyst according to claim 4, characterized in that, Co in the active ingredient x Cr y O z The loading on the foamed metal is 40-200 mg / cm³. 2 .
6. The electrocatalyst according to claim 4, characterized in that, The active ingredient contains metal Pd in the Co x Cr y O z The loading capacity is 1-5 mg / cm³ 2 .
7. An electrolytic cell system for the electrocatalytic preparation of glycolate from ethylene glycol, characterized in that, It includes the electrocatalyst according to any one of claims 4-6 and the alkaline electrolyte containing ethylene glycol.
8. A method for electrocatalytically preparing glycolate from ethylene glycol, characterized in that, Includes the following steps: An anode catalyst, a cathode catalyst, and an alkaline electrolyte containing ethylene glycol are assembled into a two-electrode electrolytic cell. An electrocatalytic reaction is carried out by applying a voltage, and the ethylene glycol is oxidized at the anode to form glycolate. The anode catalyst is the electrocatalyst according to any one of claims 4-6.
9. A method for electrocatalytically preparing glycolate from ethylene glycol, characterized in that, Includes the following steps: A three-electrode electrolytic cell is assembled with a working electrode, a counter electrode, a reference electrode, and an alkaline electrolyte containing ethylene glycol. An electrocatalytic reaction is carried out by applying voltage, and the ethylene glycol is oxidized to glycolate at the working electrode. The working electrode comprises the electrocatalyst according to any one of claims 4-6.
Citation Information
Patent Citations
Anode catalyst and system for preparing glycollic acid through electro-catalysis of ethylene glycol and method for preparing glycollic acid through electro-catalysis of ethylene glycol
CN115992368A
Cobalt chromite nanoparticles, methods of their preparation and uses thereof
WO2021102565A1